Evaluation of the Implementation of Government Policy on the Provision of Goods and Services at the Public Works and Spatial Planning Department of Banggai Regency - Ade Putra Ode Amane; Haminun Dg. Matorang; La Ode Sabirila Jayalangi; Sahraen Sibay; Wildan Zaman; Nurarifin Hi Mufti (Journal of Politica Governo, 2025)
The provision of government goods and services plays a strategic role in supporting national development and economic growth. However, in practice, problems such as fraud, inefficiency, and weak policy implementation are still common. This study aims to evaluate the implementation of government policies in the provision of goods and services at the Public Works and Spatial Planning Agency of Banggai Regency. The focus of this research is to assess the effectiveness of existing policies and regulations and identify factors influencing their implementation in the field. A qualitative approach was used, with data collection techniques including observation, documentation, and in-depth interviews. Three informants were selected through purposive sampling based on their respective areas of responsibility within the Public Works and Spatial Planning Agency of Banggai Regency. The research findings are expected to provide an overview of the strengths and weaknesses in the implementation of goods and services procurement policies, as well as provide recommendations for improving governance. Furthermore, this study is expected to contribute as a reference for further research in the field of public policy, particularly procurement.